2016
DOI: 10.1371/journal.pntd.0005219
|View full text |Cite
|
Sign up to set email alerts
|

CD4/CD8 Ratio and KT Ratio Predict Yellow Fever Vaccine Immunogenicity in HIV-Infected Patients

Abstract: BackgroundHIV-infected individuals have deficient responses to Yellow Fever vaccine (YFV) and may be at higher risk for adverse events (AE). Chronic immune activation–characterized by low CD4/CD8 ratio or high indoleamine 2,3-dioxygenase-1 (IDO) activity—may influence vaccine response in this population.MethodsWe prospectively assessed AE, viremia by the YFV virus and YF-specific neutralizing antibodies (NAb) in HIV-infected (CD4>350) and -uninfected adults through 1 year after vaccination. The effect of HIV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 38 publications
8
39
1
2
Order By: Relevance
“…Here, we observed lower, albeit not statistically significant, median anti-PfCSP titres in the HPgV-1 positive versus the negative group at baseline and 14 days past last vaccination. These observations mirror findings by Avelino-Silva et al, who showed no association between HPgV-1 infection status/viremia with yellow fever specific neutralizing antibody titres in HIV-1 positive individuals immunized with yellow fever vaccine [ 82 ]. While studies have extensively tried to understand potential inhibition mechanisms induced by HPgV-1 (and other Flaviviruses) on T cell activation [ 77 , 83 ], activation pathways that might be affected in B cells are less explored.…”
Section: Discussionsupporting
confidence: 87%
“…Here, we observed lower, albeit not statistically significant, median anti-PfCSP titres in the HPgV-1 positive versus the negative group at baseline and 14 days past last vaccination. These observations mirror findings by Avelino-Silva et al, who showed no association between HPgV-1 infection status/viremia with yellow fever specific neutralizing antibody titres in HIV-1 positive individuals immunized with yellow fever vaccine [ 82 ]. While studies have extensively tried to understand potential inhibition mechanisms induced by HPgV-1 (and other Flaviviruses) on T cell activation [ 77 , 83 ], activation pathways that might be affected in B cells are less explored.…”
Section: Discussionsupporting
confidence: 87%
“…Here, we observed lower, albeit not statistically significant, median anti-CSP titres in the HPgV-1 positive versus the HPgV-1 negative group at baseline and 14 days past last vaccination. These observations mirror findings by Avelino-Silva et al, who found no association between HPgV infection status/viremia with yellow fever specific neutralizing antibody titers in HIV-1 positive individuals immunized with yellow fever vaccine [83]. While studies have extensively tried to understand potential inhibition mechanisms induced by HPgV-1 (and other Flaviviruses) on T cell activation [78,84] activation pathways that might be affected in B cells are less explored.…”
Section: Studies In Neighbouring Countries Including Cameroon the Desupporting
confidence: 76%
“…There is an ever increasing knowledge base regarding the biochemistry of the immune response during infections and inflammatory diseases. A shift in the Th1 and Th2 responses generally results in up-regulation of Th2-type pro-inflammatory cytokines with bacterial infections [ 26 , 27 ], viral infections [ 28 , 29 ], and parasitic invasions [ 30 ]. In addition local immune responses, such as in the lung [ 31 ], brain [ 32 ], and the intestine in inflammatory bowel disease (Crohn's Disease and Ulcerative Colitis) [ 33 ] elicit alterations in the Th1 and Th2 cytokine responses.…”
Section: Discussionmentioning
confidence: 99%